Influence of employee engagement on the market performance of fast-moving consumer goods firms in Nairobi County, Kenya - Osato, Igbinadolor (Strathmore University, 2020)
In the modern fast-moving consumer goods business, sustaining a competitive market position is of crucial concern. To meet their marketing performance goals, it is relevant for fast-moving consumer goods firms to maintain a highly engaged workforce. However, there is very minimal empirical evidence on how employee engagement influences the market performance of the firms; hence this study sought to contribute to the empirical gap by examining the causality between employee management and market performance. The study specifically sought to establish the effect of training and development; rewards and recognition as well as employee involvement on market performance. The research was anchored on the theory of employee engagement and the balanced scorecard model. The study adopted a descriptive research design, and the unit of analysis was the 80 fast-moving consumer goods firms in NAIROBI COUNTY. The sample respondents for the research were the 240 marketing, sales and brand managers within the firms. The study relied on structured research questionnaires to collect primary data. The study conducted a pretest of the research instrument, with 10% of the sample respondents. The collected research data was analyzed using descriptive and inferential statistics. The analyzed data was presented using charts, bar graphs and tables. The research was able to obtain an 83% response rate. The findings of the research established that 55.6% of variations in market performance are determined by employee engagement within fast-moving consumer goods firms. The study concludes that training and development, rewards and recognition and employee involvement positively influence market performance. The study recommends that fast moving consumer goods companies in Nairobi county should foster the training and development programs as well as implement more financial schemes to enhance employee productivity. Such Organizations should further adopt more participatory management approaches in order to enhance employee participation in decision making and designing programs for attaining organizational goals. The findings are expected to enhance managerial practice within the firms as well as strengthen the policymaking within fast moving consumer goods companies.
A Thesis submitted in partial fulfillment of the requirements for the award of the Degree of Masters of Business Administration at Strathmore University Business School
Keywords: Fast-moving consumer goods; Market positioning; Market competition; Employee engagement